Moderne schilderkunst in België (de). - Eemans, M. (Hasselt : Uitgeverij Heideland - Orbis, 1969)
Van den Abeele, Albijn ; Agneessens, Edouard ; Albert, Jos ; Alechinsky, Pierre ; Van Anderlecht, Englebert ; Artan, Louis ; Van Assche, Henri ; Baertsoen, Albert ; Baes, Rachel ; Baron, Théodore ; Baseleer, Richard ; Baugniet, Charles ; Baugniet, Marcel-Louis ; Bellis, Hubert ; Berchmans, Emile ; Bergen, Emiel ; van den Berghe, Frits ; Bertrand, Gaston ; Beyns, Freddy ; Bilcke, Ferdinand ; Boch, Anna ; De Boeck, Felix ; Bonnet, Anne ; de Bosschère, Jean ; Bossuet, François ; Boulenger, Hippolyte ; Boulez, Jules ; Bouvier, Arthur ; De Braekeleer, Ferdinand ; De Braekeleer, Hendrik ; Van den Branden, Guy ; Van Breedam, Camiel ; Broodthaers, Marcel ; Brun, Charles Le ; Brusselmans, Jean ; De Bruycker, Jules ; Buisseret, Louis ; Burssens, Jan ; Bury, Pol ; Buysse, Georges ; De Caisne, Henri ; Van Camp, Camille ; Camus, Gustave ; Cantens, Maurice ; Ciamberiani, Albert ; Claus, Emile ; Clays, Paul-Jean ; Closon, Henri-Jean ; Cluysenaar, Alfred ; Cobbaert, Jan ; De Cock, Cesar ; De Cock, Xavier ; Cockx, Philibert ; Collignon, Georges ; Coosemans, Joseph ; Counhaye, Charles ; Courtens, Frans ; Cox, Jan ; Crabeels, Florent ; Creten, Georges ; Creuz, Serge ; Creytens, Julien ; Crommelynck, Albert ; Daenens, Albert ; Van Damme, Suzanne ; Dasnoy, Albert ; Degouve de Nuncques, William ; Delahaut, Jo ; Delbeke, Louis ; Delmotte, Marcel ; Delvaux, Edouard ; Delvaux, Paul ; Delville, Jean ; Delvin, Jean ; Devos, Léon ; Van Dijck, Albert ; Donas, Marthe ; Donnay, Auguste ; Van Dooren, Edmond ; Doudelet, Charles ; Drybergh, Charles ; Dubail, Berthe ; Dubois, Louis ; Ducq, Joseph-François ; Dudant, Roger ; Dufrane, Paul ; Dumont, Gilberte ; Van Dyck, Antoon ; Elias, Etienne ; Elseviers, Raymond ; Engel-Pak ; Ensor, James ; Evenepoel, Henri ; van Eyck, Jan ; Fabry, Emile ; etc.
boek